Use of Social Determinants of Health Screening among Primary Health Care Nurses of Developed Countries: An Integrative Review - Deirdre A. McGowan; Carey Mather; Christine Stirling (Nursing Reports, 2023)
The aims of the study are to evaluate and synthesise research that has investigated social determinants of health screening by primary healthcare nurses; how and when primary health care nurses perform social determinants of health screening; and implications for advancing nursing practice. Systematic searches in electronic databases identified fifteen published studies which met the inclusion criteria. Studies were synthesised using reflexive thematic analysis. This review found little evidence of primary health care nurses using standardised social determinants of health screening tools. Eleven subthemes were identified and collapsed into three main themes: organisation and health system supports are required to enable primary health care nurses; primary health care nurses are often reluctant to perform social determinants of health screening; and the importance of interpersonal relationships for social determinants of health screening. The social determinants of health screening practices of primary health care nurses are poorly defined and understood. Evidence suggests that primary health care nurses are not routinely using standardised screening tools or other objective methods. Recommendations are made for valuing therapeutic relationships, social determinants of health education and the promotion of screening by health systems and professional bodies. Overall, further research examining the best social determinant of health screening method is required.